Response to Vitamin B12 and Folic Acid in Myalgic Encephalomyelitis and Fibromyalgia - Regland, Björn; Forsmark, Sara; Halaouate, Lena; Matousek, Michael; Peilot, Birgitta; Zachrisson, Olof; Gottfries, Carl-Gerhard (PLOS ONE, 2015)
Background Patients with myalgic encephalomyelitis (ME, also called chronic fatigue syndrome) may respond most favorably to frequent vitamin B12 injections, in vital combination with oral folic acid. However, there is no established algorithm for individualized optimal dosages, and rate of improvement may differ considerably between responders. Objective To evaluate clinical data from patients with ME, with or without fibromyalgia, who had been on B12 injections at least once a week for six months and up to several years. Methods 38 patients were included in a cross-sectional survey. Based on a validated observer’s rating scale, they were divided into Good (n = 15) and Mild (n = 23) responders, and the two groups were compared from various clinical aspects. Results Good responders had used significantly more frequent injections (p<0.03) and higher doses of B12 (p<0.03) for a longer time (p<0.0005), higher daily amounts of oral folic acid (p<0.003) in good relation with the individual MTHFR genotype, more often thyroid hormones (p<0.02), and no strong analgesics at all, while 70% of Mild responders (p<0.0005) used analgesics such as opioids, duloxetine or pregabalin on a daily basis. In addition to ME, the higher number of patients with fibromyalgia among Mild responders was bordering on significance (p<0.09). Good responders rated themselves as “very much” or “much” improved, while Mild responders rated “much” or “minimally” improved. Conclusions Dose-response relationship and long-lasting effects of B12/folic acid support a true positive response in the studied group of patients with ME/fibromyalgia. It’s important to be alert on co-existing thyroid dysfunction, and we suspect a risk of counteracting interference between B12/folic acid and certain opioid analgesics and other drugs that have to be demethylated as part of their metabolism. These issues should be considered when controlled trials for ME and fibromyalgia are to be designed.